103 Prevalence And Significance Of Anterior T Wave Inversion In Females. (31st May 2014) - Malhotra, Aneil; Dhutia, Harshil; Gati, Sabiha; Dores, Helder; Millar, Lynne; Merghani, Rajay; Merghani, Ahmed; Walker, Michael; Papadakis, Michael; Sharma, Sanjay
Abstract : Purpose: Anterior T wave inversion (V1-V4) is the hallmark of arrhythmogenic right ventricular cardiomyopathy (ARVC). However, it is widely perceived that anterior T wave inversion is also common in female individuals. Previous studies in small cohorts of female athletes have demonstrated a highly variable prevalence of anterior T wave inversion of up to 14%. This study investigated the prevalence and significance of anterior T wave inversion in a large, unselected cohort of female athletic and non-athletic individuals who underwent cardiac screening. Methods: Between May 2007 and September 2013, 17, 708 individuals (n = 5, 234; 29.6% females) aged 14–35 underwent cardiac screening with health questionnaire, 12-lead ECG and consultation with a cardiologist. Further evaluation was dictated by initial results. The ECGs of female subjects were analysed placing emphasis on the presence of anterior T wave inversion, defined as T wave inversion in ≥2 contiguous anterior leads. Results: T wave inversion was present in 322 (6.2%) females, the majority confined to the anterior leads; 73% anterior, 14% lateral, 13% inferior. Anterior T wave inversion was more prevalent in competitive athletes compared to non-athletes (7.02 vs 3.78%, p < 0.001) and in black females compared to white females (14.62 vs 4.21%, p < 0.001). Anterior T-wave inversions persisted in 5.29% of females >16 years of age. The majority of anterior T wave inversion (n = 171; 73%) was confined to leads V1-V2, with only 1.2% of females exhibiting T wave inversion beyond V2, raising the suspicion of ARVC. Multivariate analysis identified black ethnicity as the sole, independent predictor for the presence of anterior T wave inversion (OR 3.1, 95% CI 1.2–8.4, p = 0.03). Conclusion: In the largest unselected cohort of females to date, the overall prevalence of anterior T wave inversion was higher (4.5%) than those in previously reported studies. This was also the case for females of Caucasian ethnicity. Anterior T wave inversion persisted in a considerable proportion of females >16 years, excluding the 'juvenile' pattern. Although we did not identify ARVC in any females with anterior T wave inversion, given the low prevalence of T wave inversion beyond V2, particularly in Caucasian individuals (1.06%), such patterns not be considered a normal finding and should trigger further clinical evaluation.